The anthropogenic activities in Makere north forest reserve in Tanzania and implications to conservation - Eberehard Daudi; Hussein Luswaga; Pensia Mapunda; Hamisi Nchimbi (Global Ecology and Conservation)
Reserved forests play a vital role in the provision of ecosystem services although the majority of them in low-economy countries like Tanzania experience pressure from direct anthropogenic activities causing deforestation and degradation. The loss of forests undermines their functioning, hence the poor delivery of forest benefits. Although the generic causes of deforestation and degradation are known, their extent and variation are site-specific. Particularly, the dynamics of direct anthropogenic activities in forests are under-studied in the Makere forest reserve in Tanzania. This study aimed to estimate the extent and diversity of direct anthropogenic activities in Makere North Forest Reserve (MNFR) Tanzania and its implications for conservation. Field data were collected from 120 field plots of 800 m2 (0.08 hectare) sizes in three (3) forest study sites bordering Makere, Nyamidaho, and Mvugwe villages. The cross-sectional study design applied a mixed-method approach to quantify and qualify the extent and situation of direct anthropogenic activities in MNFR. The findings indicate that proportions of plots affected by direct anthropogenic activities were logging (79 %), wildfire (51 %), charcoal making (48 %), livestock grazing (35 %), footpaths (34 %), and agriculture (32 %) with beekeeping and firewood collection having lower proportions of plots affected of 03 % and 19 % respectively. However, these proportions were not significantly different between the study sites (x2=0.597, d.f=2, p = 0.7419). The diversity of direct anthropogenic activities was slightly higher for Makere (Shannon-Wiener index, H= 3.211), followed by Nyamidaho (H=3.168) and least for Mvugwe (H=3.074) with overall average diversity at H= 3.151. The average of direct anthropogenic activities per hectare was logging (95 stumps, diameter>5 cm), agriculture (25.7 % cultivated field), firewood collection (16 stumps, diameter ≤5 cm), charcoal making (17 charcoal kilns), beekeeping (0.4 beehives) and footpaths (6 trails). The extent of agriculture and firewood collection per hectare were not significantly different between the study sites (p = 0.4441 and p = 0.5797 respectively). On the other hand, the extent of logging, charcoal-making, beekeeping, and footpaths per hectare significantly differed between the study sites at p = 0.0001, p = 0.0002, p = 0.0473, and p = 0.0336 respectively. The results imply that the extent of threatening anthropogenic activities in MNFR is high, thus undermining conservation and making it harder to achieve efficiently the management objectives.